2013
DOI: 10.1017/s1431927613006302
|View full text |Cite
|
Sign up to set email alerts
|

Xe+ FIB Milling and Measurement of Amorphous Silicon Damage

Abstract: Minimizing surface damage during FIB specimen preparation is an important factor for high quality analytical results, especially in the case of TEM membrane and EBSD sample preparation. For conventional Ga + FIB milling, techniques using reduced accelerating voltages for final polishing to minimize sample damage are commonly used [1]. With newer ion species available for FIB milling, namely Xe + , the ion-solid interaction will be slightly different from Ga+, but the same low ion energy strategies can be appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 0 publications
0
37
0
Order By: Relevance
“…The PFIB is capable of much higher ion beam currents (few pA to >1 μA) compared to Ga-FIB (1pA to 20nA), and retains a focused spot size unlike Ga+ at high ion beam currents to enable thin slicing (Smith et al, 2006). The PFIB also maintains a quality surface for imaging, with the amount of surface amorphization decreased by 20-40% on silicon compared to Ga + -FIB (Kelley et al, 2013), and the surface roughness reduced by an order of magnitude (from 400 to 50 nm RMS on interconnects) when using a rocking polish (Altmann and Young, 2014). These potential benefits translate for biological imaging in 3D, ultimately offering possibility for larger, smoother, and less damaged volumes to be acquired by the PFIB in shorter times with the same nanoscale resolution as images afforded by the Ga + FIB-SEM (Bassim et al, 2014;Burnett et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The PFIB is capable of much higher ion beam currents (few pA to >1 μA) compared to Ga-FIB (1pA to 20nA), and retains a focused spot size unlike Ga+ at high ion beam currents to enable thin slicing (Smith et al, 2006). The PFIB also maintains a quality surface for imaging, with the amount of surface amorphization decreased by 20-40% on silicon compared to Ga + -FIB (Kelley et al, 2013), and the surface roughness reduced by an order of magnitude (from 400 to 50 nm RMS on interconnects) when using a rocking polish (Altmann and Young, 2014). These potential benefits translate for biological imaging in 3D, ultimately offering possibility for larger, smoother, and less damaged volumes to be acquired by the PFIB in shorter times with the same nanoscale resolution as images afforded by the Ga + FIB-SEM (Bassim et al, 2014;Burnett et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been clearly demonstrated that the use of Xe + ions results in a reduced depth of amorphisation when compared to Ga + FIB [26,27]. The efficient sputtering rate and relatively high operating currents make the Xe + PFIB an ideal candidate for the fabrication of mesoscale tensile specimens.…”
Section: Introductionmentioning
confidence: 99%
“…This difference corresponds to a variation of nearly 40 MPa, with the specimens prepared using PFIB having the largest yield shift. Although the samples prepared using PFIB accumulate some surface damage due to ion beam milling, previous observations have shown that the damage layer is approximately 40% shallower compared to that induced using Ga + FIB, being in the order of 10 s of nano meters 43,44 . This represents approximately 5 × 10 −3 % of the sample volume which is not thought to contribute significantly to the measured shift.…”
Section: Discussionmentioning
confidence: 92%